Rails, Angular, Postgres, and Bootstrap : powerful, effective, and efficient full-stack web development - Copeland, David (David Bryant) (Pragmatic programmers., 2016)
As a Rails developer, you care about user experience and performance, but you also want simple and maintainable code. Achieve all that by embracing the full stack of web development, from styling with Bootstrap, building an interactive user interface with AngularJS, to storing data quickly and reliably in PostgreSQL. Take a holistic view of full-stack development to create usable, high-performing applications, and learn to use these technologies effectively in a Ruby on Rails environment--